How do glucocorticoids regulate lipid metabolism? - Guia, Roldan M. de; Herzig, Stephan (Glucocorticoid signaling, 2015)
Glucocorticoids (GCs) and their cognate, intracellular receptor, the glucocorticoid receptor (GR) have been characterized as critical checkpoints in the hormonal control of energy homeostasis in mammals. Whereas physiological levels of GCs are required for proper metabolic control, aberrant GC action has been linked to a variety of severe metabolic diseases, including type 2 diabetes and obesity. As a member of the nuclear receptor superfamily of transcription factors, the GR translocates into the cell nucleus upon GC binding where it serves as a transcriptional regulator of distinct GC-responsive target genes that are in many cases associated with lipid regulatory pathways and thereby intricately control both physiological and pathophysiological systemic lipid homeostasis. Thus, this chapter focuses on the current knowledge of GC/GR function in lipid handling and its implications for systemic metabolic dysfunction.